Exploring the pathological role of intervertebral disc and facet joint in the development of degenerative scoliosis by biomechanical methods. (December 2019) - Zheng, Jie; Yang, Yonghong; Cheng, Boyle; Cook, Daniel
Abstract: Background: To investigate the biomechanical changes in the development of scoliosis due to intervertebral disc and facet joint degeneration. Methods: We enrolled 39 cases of fresh-frozen lumbar spine specimens and underwent CT scanning and 3D reconstruction. An Osirix Dicom imaging system was to assess the degeneration of the intervertebral disc and facet joints, and mechanical loading was conducted using a spine mechanical instrument with the frequency set at plus/minus 7.5 NM, 0.005 Hz. Range of motion (ROM) and neutral zone (NZ) of 39 cadaveric lumbar spines were tested. Findings: Degeneration existed in all 39 cases of the lumbar specimens: the Cobb angle >10° in 5 cases (degenerative scoliosis (DS) group), between 3° and 10° in 9 cases (pre-degenerative scoliosis (PS) group) and <3° in 25 cases (no scoliosis (NS) group). The axial torsion (AT) range of motion (ROMAT ) and the NZ of the DS and PS groups was greater than in the NS group and increased with increasing Cobb angle. A significant correlation was found between the degeneration of the intervertebral disc and the AT and the AT correlated with the Cobb angle and facet joint degeneration. Interpretation: The AT correlated with intervertebral disc and facet joint degeneration, which might be a mechanic factor in the occurrence and development of degenerative scoliosis. Highlights: Axial torsion was increased with the increase in scoliosis angle. Axial torsion was high in pre-degenerative and degenerative scoliosis. Axial torsion correlates with intervertebral disc and facet joint degeneration.